Experimental screening studies on rabies virus transmission and oral rabies vaccination of the Greater Kudu (Tragelaphus strepsiceros). Issue 1 (December 2018) - Hassel, Rainer; Vos, Ad; Clausen, Peter; Moore, Susan; Westhuizen, Jolandie; Khaiseb, Siegfried; Kabajani, Juliet; Pfaff, Florian; Höper, Dirk; Hundt, Boris; Jago, Mark; Bruwer, Floris; et al.
Abstract Rabies in the Greater Kudu (Tragelaphus strepsiceros) in Namibia is unique and found in such magnitude as has not been reported elsewhere in southern Africa. Reasons as to why Kudus appear to be exceptionally susceptible to rabies still remain speculative at best. Because the current severe rabies endemic in Kudus continues to have an enormous negative impact on the Namibian agricultural sector, we set out to question existing dogmas regarding the epidemiology of the disease in a unique experimental setting. In addition, we explored effective measures to protect these antelopes. Although we were able to confirm high susceptibly of kudus for rabies and sporadic horizontal rabies virus transmission to contact animals, we contend that these observations cannot plausibly explain the rapid spread of the disease in Kudus over large territories. Since parenteral vaccination of free-roaming Kudus is virtually impossible, oral rabies vaccination using modified life virus vaccines with a high safety profile would be the ultimate solution to the problem. In a proof-of-concept study using a 3rd generation oral rabies virus vaccine construct (SPBN GASGAS) we found evidence that Kudus can be vaccinated by the oral route and protected against a subsequent rabies infection. In a second phase, more targeted studies need to be initiated by focusing on optimizing oral vaccine uptake and delivery.